Should we go “green”, or should we deal with it as a trend that is going to pass? Evaluating the benefits of Green Human Resources Management (GHRM) on workers’ attitudes and behavior - Gomes, Daniel; Ribeiro, Neuza; Gomes , Gabriela; Ortega , Eduardo; Santos , Eleonora (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Green Human Resources Management (GHRM) has emerged as a response to the growing need for companies to include environmental sustainability in their business models and in their management practices. In particular, in the tourism industry, organizations are under internal and external pressure to protect the environment. Thus, as environmental issues become part of organizational strategy to achieve goals in companies, GHRM has become a strategic tool for practitioners (Tanova & Bayighomog, 2022), arising especially from the need to address the increasing role of human resource management in the evolution of companies, namely through more sustainable business (Haldorai et al., 2022), incorporating in that management more green issues and oriented towards strategic environmental goals (Ren et al., 2022). This research seeks to examine how GHRM can impact on employee’s attitudes and behavioral intentions. More specifically, this study aims to understand (1) the effect of GHRM on affective commitment; (2) the effect of GHRM on turnover intention; (3) the mediating role of affective commitment in the relationship between GHRM and turnover intention. Data were collected through an online questionnaire, from 132 employees who had been working in several Portuguese tourism organizations for at least 6 months. GHRM was measured through six items based on studies by Kim et al. (2019), Shen and Benson (2016), and Hsiao et al. (2014). Three items proposed and validated by Rego et al. (2011) were used to measure affective commitment. And turnover intention was assessed using a 4-item measure based on the study by Bishop et al. (2002) and Mobley (1988). Results suggest that when organizations apply greener HRM practices, they can positively influence their employees' actions, improving their affective attachment to the organization and, consequently, their intentions towards their work, thus contributing positively to the organization and society. The growing concern for environmental issues has led researchers to focus their research there, which according to Renwick et al. (2013) and Ahmad et al. (2021) is still not enough, especially when it comes to GHRM. Thus, in addition to trying to reduce this gap in the literature, this study is innovative by integrating the effect of GHRM on affective commitment and turnover intention, inserting these variables into a single research model, expanding knowledge on the topic. Furthermore, this analysis contributes to help shape how organizations position themselves in relation to the environment (Jabbour, 2013), suggesting that they should adopt GHRM practices to implement green policies more effectively and efficiently, especially that strengthen employees' affective attachment and promote green behaviors among employees and towards the organization. These are important findings, particularly, for the hospitality and tourism industry because some main reasons: (1) most hotels are under high pressure to protect the environment through environment-friendly services; (2) turnover constitutes a traditionally serious problem in the Portuguese hospitality and tourism industry; (3) a committed workforce currently emerges as a challenge for the balance of organizations of hospitality and tourism industry. This study presents some limitations and suggests avenues of future research on the impact of GHRM, namely in other psychosocial variables. The use of cross-sectional data prevented the drawing of conclusions on the causality nexus between the variables. Indeed, the data were collected at a single moment in time and through the same source, which may cause a bias due to common-method variance (Podsakoff et al., 2003). Therefore, more in-depth longitudinal research is needed to reach more valid conclusions about causality and to prevent risks of common-method bias. However, we can presume that the effects of GHRM can be very successful if they are well accepted by employees, especially by those who are aligned with the sustainable goals of the organization. Consequently, the affective bond exerts a significant and positive impact on the relationship between GHRM and Turnover Intention, reduces its negative impact, and reinforces the positive aspects of the correct and appropriate implementation of GHRM. In conclusion, this study suggests that when organizations apply a greener HRM, they might influence positively the attitudes and behaviors of their employees, and, thus, contribute positively to the organization and to society.